Bladder irrigation with Chlorhexidine reduces bacteriuria in persons with spinal cord injury - Madeleine Wikström; Richard Levi; Wolfram Antepohl (Medical Journals Sweden, 2018)
Objective: To explore whether bladder irrigation with chlorhexidine: (i) can reduce bacteriuria, and (ii) is a practically feasible option in subjects with spinal cord injury practicing intermittent self-catheterization. Design: A prospective, non-controlled, open, multi-centre study. Methods: Fifty patients with spinal cord injury, practicing intermittent self-catheterization, with a history of recurrent urinary tract infections were screened for bacteriuria at follow-up visits to 4 spinal cord injury centres in Sweden. Twenty-three patients had a positive urine culture (> 105 CFU/ml of > 1 bacterial species), of which 19 completed the study. Subjects proceeded with bladder irrigation, using 120 ml of 0.2% chlorhexidine solution twice daily for up to 7 days. Urine samples were taken twice daily. Response to treatment was defined as reduction in bacterial counts to < 103 CFU/ml. Results: Fourteen of 19 subjects reduced their bacterial counts to or below the set limit. Subsequent return of above-endpoint bacteriuria was seen in most of the subjects. However, there were significantly fewer subjects with bacteriuria after treatment (p < 0.005). Conclusion: Bladder irrigation with chlorhexidine, using intermittent self-catheterization, reduced bacteriuria in the majority of subjects with spinal cord injury and bacteriuria. The addition of bladder irrigation was practically feasible in the short time-frame of this study.